Sejarah Lokal dan Public history (Sejarah Bagi Masyarakat) - Jumardi Jumardi (CHRONOLOGIA, 2022)
The correlation between local history and national history is very strong, because national history is generally formed from various combinations of existing local histories. The main focus of local history is not much different from national history, starting from the role of the people, whether religious leaders or local leaders who were involved in the struggle against the invaders or other important roles that deserve to be considered as one of the historical events. Apart from character, other themes that can be identified in local history are institutions, the general public involved in important events and the geography of a particular area. Despite having a broad study and close meaning to the value of people's lives, it cannot be denied that there are still many who underestimate local history. On the other hand, there are still many who assume that local studies have high difficulties in validating the data. In order to maintain this, this research was conducted. On the other hand, this research also aims to enrich information about local history so as to increase love for the country and nation. In order to obtain valid results, in this study a qualitative descriptive analysis method was applied. For data collection techniques themselves, using library instruments and documentation. The results of this study found that national history is an extension of local history, the link between local history and public history, as well as the benefits of local history for the Indonesian people.